(untitled) (Journal of Hama University, 2025)
The research aimed to reveal the degree of cybersecurity awareness among a sample of Hama University students from their point of view, as well as to reveal the significance of the differences between the average scores of the research sample members on the cybersecurity awareness questionnaire due to the variables (school year - academic specialization(,The descriptive analytical method and the questionnaire were used as a tool for collecting data. The research sample consisted of (273) male and female students from the University of Hama, who were selected by the available random method. The most important results reached by the research are the following: 1- The degree of awareness of cybersecurity among a sample of Hama University students, from their point of view, reached a high degree. 2-There are statistically significant differences between the averages of the research sample members’ answers to the cybersecurity awareness questionnaire due to the academic year variable, in favor of final year students. 3- There are statistically significant differences between the averages of the research sample’s responses to the cybersecurity awareness questionnaire due to the academic specialization variable, for the benefit of students in scientific colleges.